A Proposed Program to Audit the Effects of Indirect Emissions According to the Standard of Assurance Correlations (3410) on the Environment - Mahmood , Mohammed Ali; Hamdan, Khawla Hussein (Journal of Ecohumanism, 2025)
Global warming is one of the phenomena that affect the environment as a result of greenhouse gases, as indirect emissions represent 80% of the total global emissions, so organizations and professional councils, including the ISO Organization and the Council of the Accounting and Auditing Profession, sought to issue a standard of confirmation links by issuing a standard (3410) to provide guidance to the auditor when auditing the effects of indirect emissions on the environment, so the research sought To identify the standard of confirmation correlations (3410), environmental effects and their elements, relevant laws and instructions and international agreements to which Iraq has joined, then prepare a proposed program to audit the environmental effects of greenhouse gases for indirect emissions of the two bands (3 and 2) according to the standard of confirmation correlations 3410, which contributes to determining the effectsof emissions to reduceEnvironmental impacts such as high temperatures and human health The research problem is the lack of an audit program for the effects of indirect emissions according to the standard of confirmation correlations (3410) on the environment, the research is based on the premise that the proposal of an audit program for the effects of indirect emissions contributes to determining the effects of those emissions on the environment from pollution and climate change and adopted theSecond on the laws, regulations, instructions and agreements related to the subject of research and ISO standards The research has reached a set of conclusions, the most important of which is that the federal financial control debt program did not include did not take into account the standard of linkages (3410) The most important recommendations that the proposed program contributes to determining the environmental effects and thus contribute to its reduction.